AHP-COPRAS Model for Determination of Suitability of Surveyor Assignment for Survey of New Building Ships at PT. BKI Main Branch Surabaya - Bakti Nugroho Dwi Kushadianto; Udisubakti Ciptomulyono (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The purpose of this study is to (1) identify the criteria used as the basis for selecting surveyors who will conduct a survey of new building ships at new shipbuilding yards in East Java, (2) develop a measurement of the level of conformity of surveyors to survey activities of new building ships at new shipbuilding yards in East Java, and (3) provide recommendations for the assignment of surveyors who handle surveys of new building ships at new shipbuilding yards in East Java. Design/methodology/approach: The model used in this study is the AHP–COPRAS model, which is combined to select surveyors who will survey a new shipbuilding yard. First, the results of AHP processing will be separated for each shipyard class to know each shipyard's criteria and alternative weights. The next stage is an analysis using COPRAS. The questionnaire used to collect COPRAS data uses an ordinal scale. Respondents who will be involved in filling out the COPRAS questionnaire are surveyors at BKI Main Branch Surabaya. Next, COPRAS assesses each surveyor using the criteria and alternatives identified in the AHP process. Calculations on COPRAS also use the weights that have been generated from the AHP. At the final stage, different scores will be obtained for each surveyor for each class of shipyard under study. Findings: The highest utility value in Shipyard 1 was found in JX surveyors with a utility of 100%. Thus, at shipyard 1 the JX surveyor is the surveyor who is considered the most suitable to survey building ships at PT. BKI Main Branch Surabaya. The highest utility value in Shipyard 2 is found in surveyor AX with a utility of 100%. Thus, at Shipyard 2, the AX surveyor is the surveyor who is considered the most suitable for surveying shipbuilding at PT. BKI Main Branch Surabaya. The highest utility value at Shipyard 3 is found in JX surveyors with a utility of 100%. Thus, at Shipyard 3 the JX surveyor is the surveyor who is considered the most suitable to conduct a shipbuilding survey at PT. BKI Main Branch Surabaya. Paper type: Research paper